DETERMINATION OF PHARMACOKINETIC PARAMETERS FROM DISTRIBUTION STUDY FOLLOWING DEVELOPMENT AND VALIDATION OF A SENSITIVE LC-MS METHOD IN TISSUE MATRICES FOR 2-(4-ETHOXYPHENYLSULPHONAMIDO) PENTANEDIAMIDE, AN INVESTIGATIONAL ANTICANCER AGENT - YEASMIN, NILUFA; MISHRA, SUVASISH; SEN, SUBRATA (International Journal of Applied Pharmaceutics, 2024)
Objective: The aim of this study was to develop and validate bioanalytical methods for estimation of 2-(4-ethoxyphenyl sulphamido) pentanediamide (PC), an investigational anticancer agent, in various organ/tissue matrices to study various Pharmacokinetic parameters using lC-MS. Methods: Freshly prepared tissue homogenates from Sprague-Dawley rats were used as matrices to develop the bioanalytical method in lC-MS to determine Cmax, Tmax, AUC0-t, AUC0-inf, T1/2, and mean Residence Time (MRT). The distribution study was conducted by administering PC orally to Sprague-Dawley rats and quantifying PC in different excised organs at different points. A non-compartmental analysis was done using ‘PK solver’ software. Results: In all the tissue matrices, the concentrations of PC were found in the linear range of 10 to 5000 ng/ml. High level of precision, accuracy, and recovery, with negligible matrix effects, were found. PC was distributed in all tissues except the brain. Pharmacokinetic parameters such as Tmax and MRT were between 1.11±0.12 to 2.33±0.11 h and 2.17±0.16 to 4.01±0.25 h respectively in the liver, lung, heart, spleen, kidney, and thymus. Conclusion: Simple and sensitive lC-MS methods for PC in different tissue matrices were developed and validated. As PC does not cross Blood Brain Barrier (BBB), it will not adversely affect Central Nervous System (CNS). PC is absorbed fast from Gastro Intestinal Tract (GIT) to blood and subsequently reaches the different tissues. Consequently, a fast onset of action will be seen. To sum up, PC is a probable potential anticancer agent with no or minimal adverse effects on CNS.